Behavioral "nudges" in the electronic health record to reduce waste and misuse: 3 interventions. (15th December 2022) - Grouse, Carrie K; Waung, Maggie W; Holmgren, A Jay; Mongan, John; Neinstein, Aaron; Josephson, S Andrew; Khanna, Raman R
Abstract: Electronic health records (EHRs) offer decision support in the form of alerts, which are often though not always interruptive. These alerts, though sometimes effective, can come at the cost of high cognitive burden and workflow disruption. Less well studied is the design of the EHR itself—the ordering provider's "choice architecture"—which "nudges" users toward alternatives, sometimes unintentionally toward waste and misuse, but ideally intentionally toward better practice. We studied 3 different workflows at our institution where the existing choice architecture was potentially nudging providers toward erroneous decisions, waste, and misuse in the form of inappropriate laboratory work, incorrectly specified computerized tomographic imaging, and excessive benzodiazepine dosing for imaging-related sedation. We changed the architecture to nudge providers toward better practice and found that the 3 nudges were successful to varying degrees in reducing erroneous decision-making and mitigating waste and misuse.